"I Want to Influence More Children in the Mountains"—A Case Study of a "Zhijiao Teacher". Issue 3 (4th May 2022) - Sun, Yaling; Li, Yanling; Xu, Xianxuan; Song, Nana; Wen, Qianyao
Abstract: Drawing from the professional experience of one "zhijiao" teacher in the southwestern border of China, this study uses a narrative method to describe and analyze the growth and development of an effective teacher serving in a rural and remote school with a high concentration of ethnic minority students. Qualitative data for this single case study were generated through interviews with the selected teacher and her colleagues and students. Specifically, the study examines the teacher's professional philosophy and beliefs, professional knowledge, and professional skills. It illustrates how these domains relate to the teacher's effectiveness. The study also discusses possibilities for better preparation and development of teachers serving the most disadvantaged areas in China.